Comparison of activity test of ethanol extract and palm root infusion (Arenga pinnata) as an aphrodisiac - Rochmat, M. Idhar Khoirul; Mugiyanto, Eko; Waznah, Urmatul; Nur, Achmad Vandian (Universitas Muhammadiyah Malang, 2023)
The palm tree (Arenga pinnata) contains secondary metabolites such as saponins, phenols, triterpenoids, alkaloids, and flavonoids that can be used as medicine, particularly as an aphrodisiac. Aphrodisiacs are natural substances, medications, or herbal supplements that have the potential to increase sexual arousal. The use of herbal aphrodisiac drugs has been increasing year by year in Indonesia. This study aims to determine the aphrodisiac activity of palm root water extract (Arenga pinnata) in test animals (Web Wiester mice). The preparation of the extract begins with the processing of palm roots, which are then made into an infusion of palm root water (Arenga pinnata). The method of making the palm extract uses infusion and maceration techniques. The aphrodisiac potential test was conducted in vivo using 32 Web Wiester mice, which were divided into 5 groups; the dosage was determined by dividing the mice into five groups (positive control, negative control, 0.5 ml infusion, 1 ml infusion, and extract). The characterization of aphrodisiac properties in the extract included testing the libido of mice (Mus musculus). The results showed that the extract test group with a dose of 250 Mg/KgBW had the highest mating retention among the other test groups.